2008
DOI: 10.1089/neu.2008.0683
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Atrophy after Traumatic White Matter Injury: Correlation with Acute Neuroimaging and Outcome

Abstract: Traumatic brain injury (TBI) is a pathologically heterogeneous disease, including injury to both neuronal cell bodies and axonal processes. Global atrophy of both gray and white matter is common after TBI. This study was designed to determine the relationship between neuroimaging markers of acute diffuse axonal injury (DAI) and cerebral atrophy months later. We performed high-resolution magnetic resonance imaging (MRI) at 3 Tesla (T) in 20 patients who suffered non-penetrating TBI, during the acute (within 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0
15

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 51 publications
(52 reference statements)
8
94
0
15
Order By: Relevance
“…Volumetric analysis using specific regions has demonstrated significant decreases in volume in both adult (Tomaiuolo et al, 2004;Warner et al, 2010a;Wilde et al, 2004Wilde et al, , 2006a and pediatric (Beauchamp et al, 2010;Fearing et al, 2008;Spanos et al, 2007;Wilde et al, 2005Wilde et al, , 2006bWilde et al, , 2007Wu et al, 2010a) subjects with TBI in the chronic post-injury interval. Additionally, voxel-based, whole-surface based, and tensorbased analyses have also demonstrated significant global reductions in cortical thickness (Merkley et al, 2008) and cortical gray matter volume Ding et al, 2008;Gale et al, 2005;Warner et al, 2010a,b) as well as white matter volume (Ding et al, 2008;Sidaros et al, 2009;Vannorsdall et al, 2010). Late volumetric measures have demonstrated relation to measures of clinical severity Schonberger et al, 2009;Trivedi et al, 2007), outcome, (Ding et al, 2008;Gale and Prigatano, 2010;Warner et al, 2010b), cognition (Bergeson et al, 2004;Fujiwara et al, 2008;Himanen et al, 2005;Serra-Grabulosa et al, 2005;Tomaiuolo et al, 2004;Warner et al, 2010a), and potential for benefit from rehabilitation intervention (Strangman et al, 2010), although other studies have reported no correlation between volumetric measures and functional outcome (Anderson et al, 1995;Sherer et al, 2006;Yount et al, 2002).…”
Section: Mrimentioning
confidence: 99%
“…Volumetric analysis using specific regions has demonstrated significant decreases in volume in both adult (Tomaiuolo et al, 2004;Warner et al, 2010a;Wilde et al, 2004Wilde et al, , 2006a and pediatric (Beauchamp et al, 2010;Fearing et al, 2008;Spanos et al, 2007;Wilde et al, 2005Wilde et al, , 2006bWilde et al, , 2007Wu et al, 2010a) subjects with TBI in the chronic post-injury interval. Additionally, voxel-based, whole-surface based, and tensorbased analyses have also demonstrated significant global reductions in cortical thickness (Merkley et al, 2008) and cortical gray matter volume Ding et al, 2008;Gale et al, 2005;Warner et al, 2010a,b) as well as white matter volume (Ding et al, 2008;Sidaros et al, 2009;Vannorsdall et al, 2010). Late volumetric measures have demonstrated relation to measures of clinical severity Schonberger et al, 2009;Trivedi et al, 2007), outcome, (Ding et al, 2008;Gale and Prigatano, 2010;Warner et al, 2010b), cognition (Bergeson et al, 2004;Fujiwara et al, 2008;Himanen et al, 2005;Serra-Grabulosa et al, 2005;Tomaiuolo et al, 2004;Warner et al, 2010a), and potential for benefit from rehabilitation intervention (Strangman et al, 2010), although other studies have reported no correlation between volumetric measures and functional outcome (Anderson et al, 1995;Sherer et al, 2006;Yount et al, 2002).…”
Section: Mrimentioning
confidence: 99%
“…Extensive axonal degeneration (Bigler, 1987;Ding et al, 2008;Mamere et al, 2009) and generalized cerebral atrophy (MacKenzie et al, 2002;Sidaros et al, 2009;Trivedi et al, 2007) associated with poor functional outcomes are the common sequelae. TBI-induced hypoperfusion, which could occur beyond the site of primary injury (Bonne et al, 2003;Hofman et al, 2001;Pasco et al, 2007), aggravates this trauma-triggered brain damage.…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, the management of patients with TBI has generally concentrated on the prevention or amelioration of such devastating secondary Although mechanisms responsible for the observed therapeutic potential of MSCs remain to be explored, it is suggested that the beneficial effects are owed to the ability of MSCs to secrete an array of cytokines and trophic factors that activate endogenous restorative and regenerative processes, e.g., angiogenesis, synaptogenesis, gliogenesis, and neurogenesis (Chopp and Li, 2006;Mahmood et al, 2004aMahmood et al, , 2004b. Treatment of TBI with transplantation of MSCs may also moderate post-TBI hypoperfusion that results from impaired vasculature or disturbed hemodynamics (Hofman et al, 2001) and may reduce cerebral atrophy that occurs concomitantly with progressive neuronal loss (Immonen et al, 2009a;Smith et al, 1997) and diffuse axonal injury (Bigler, 1987;Ding et al, 2008;Mamere et al, 2009;Sidaros et al, 2009). To our knowledge, however, little is known about the dynamic effect of grafted MSCs on post-TBI hemodynamic and atrophic progression.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported disruptions in these neural processes following diffuse axonal injury (DAI), which results from shearing of white matter-connecting pathways within neural networks associated with cognitive flexibility and inhibition Berryhill et al, 1995;Kinnunen et al, 2010;Levin et al, 2004;Ryan et al, 2014;Tasker, 2006). Perhaps not surprisingly, these childhood injuries are associated with widespread morphological changes, including reductions in cortical gray and white matter, as well as overall reductions in brain volume (Beauchamp, & Ditchfield, et al, 2011;Benson et al, 2007;Bigler, 2001Bigler, , 2007Ding et al, 2008;Gale, Baxter, Roundy, & Johnson, 2005;Trivedi et al, 2007;Wilde et al, 2005).…”
Section: Significancementioning
confidence: 99%